Lingkungan Bersih Bebas Sampah: Sosialisasi dan Pelatihan Pengelolaan Sampah untuk Mewujudkan Lingkungan Bersih dan Sehat - Syabani, Muhammad William; Hakim, Arif Rahman; Norin, Husni; Maimunah, Siti; Rizky, Muhammad; Pramasti, Diva Khofiffah Zanuar; Agustina, Agustina; Febriyanti, Siti Nurhaliza; Sari, Yenni Permata (Hayak Bamara: Jurnal Pengabdian Masyarakat, 2024)
In Sungai Ramania Village, there are several issues related to environmental cleanliness. These issues are closely related to the mindset of the community and habits that do not maintain environmental cleanliness. In an effort to answer these problems, the service team came up with 4 activities related to the highlighted problems. The four activities are: (1) Socialization of household waste sorting; (2) Socialization of clean and healthy lifestyles (PHBS); (3) Cleaning up garbage; and, (4) Training in making eco-bricks as an alternative to waste management. The four programs were designed using David Easton's idea of a system. Easton says that efforts to improve living standards contain at least 3 elements of a systematic process, namely inputs, processes, and outputs. This theory is also used as a reference in analyzing performance during the implementation of the service program. This service activity was carried out in Sungai Ramania Village, Mandastana District, Barito Kuala Regency on July 16 - August 21, 2023. Although the implementation of this service program did not cause significant changes, there were gradual changes in the mindset and behavior of the community, which had implications for the environmental conditions of Sungai Ramania Village which looked cleaner. Overall, the service program that has been implemented produces outcomes in the form of growing community awareness and creativity to overcome the waste problem in the village. The realization of this service program cannot be separated from the active involvement of the community and related parties.